ANALYSIS ON LIMIT LOAD AND J-INTEGRAL FOR EMBEDDED AND PROPAGATED CRACK PLATES UNDER BIAXIAL LOADING - LV YuanJun; CHEN Qiong; ZHANG XunLei (Jixie qiangdu)
Ligament rupture occurs for embedded crack plate under biaxial loading. Then,embedded crack will propagate as surface crack,through-thickness cracks or extended surface cracks. The mechanical strength of components with different types of cracks under biaxial loading has become the focus of research. As a typical biaxial loading condition,an end tensile/compressive force applied at the centroids of the end sections of the plate perpendicular to the crack plane,a tensile/compressive stress parallel to the crack plane and a cross-thickness bending moment applied at the end sections of the plate,has been considered. Taking a plate with embedded elliptical crack is as the research object,comparison results of limit load and J-integral solutions for embedded elliptical crack,propagated surface half-elliptical crack,propagated through-thickness cracks or extended surface cracks have been given,provided basis for users to use defective components reasonably.